Candida species in patients with oral dysesthesia: A comparison of carriage among oral disease states. (18th January 2018) - Farah, Camile S.; Amos, Kate; Leeson, Rachel; Porter, Stephen
Abstract : Objectives: Oral dysesthesia (burning mouth syndrome) is characterized by a burning‐like sensation of the oral mucosa. The etiology of this disorder is still unknown, however, associations with oral fungal carriage have been proposed and applied clinically. The aim of the this study was to compare oral Candida carriage in patients with oral dysesthesia with Candida carriage in patients with other commonly diagnosed oral diseases to clarify the relationship between Candida and oral dysesthesia. Subjects and Methods: In total, 441 patients in total including 79 patients diagnosed with oral dysesthesia were included in this study. A retrospective analysis of mycological investigations undertaken in patients with clinically diagnosed oral dysesthesia compared with other oral conditions was undertaken. Results: Oral carriage of Candida was found in 63.3% (50 of 79) of patients with oral dysesthesia. The frequency of carriage and oral load of Candida were not significantly increased in patients with oral dysesthesia relative to the other conditions assessed. Patients with clinical signs of fungal infection or xerostomia presented with increased carriage of Candida . Conclusion: There is no association between oral dysesthesia and the presence or load of oral Candida .